2007
DOI: 10.1016/j.ijgo.2007.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasound and three-dimensional power Doppler in the assessment of ovarian tumors

Abstract: Evaluation by 3DUS with 3DPD improves diagnostic accuracy of ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 12 publications
(16 reference statements)
1
21
0
1
Order By: Relevance
“…They reported a sensitivity, specificity, positive predictive value, and negative predictive value of 93.5, 92.9, 84.5, and 97.2 %, respectively [34]. Several other studies provided similar results and concluded that 3D PD is a highly sensitive and specific tool for diagnosing ovarian malignancies [33,[35][36][37]. 3D USG and 3D PD technique were found to be highly reproducible [28,38].…”
Section: Oncologymentioning
confidence: 87%
“…They reported a sensitivity, specificity, positive predictive value, and negative predictive value of 93.5, 92.9, 84.5, and 97.2 %, respectively [34]. Several other studies provided similar results and concluded that 3D PD is a highly sensitive and specific tool for diagnosing ovarian malignancies [33,[35][36][37]. 3D USG and 3D PD technique were found to be highly reproducible [28,38].…”
Section: Oncologymentioning
confidence: 87%
“…When conventional ultrasound examination is not satisfactory, three-dimensional ultrasonography (3D) can be recommended as it offers superior sensitivity and specificity, described in the literature around 93.5 and 91.5% [17][18][19] (B). Magnetic resonance imaging (MRI) may be appropriate for analysis of adnexal cysts to help clarify the potential for malignancy with a sensitivity and specificity of 91.9 and 88.4%, respectively 20,21 (B).…”
Section: Laboratory and Image Aspectsmentioning
confidence: 99%
“…Metaanalysis studies on resistance index, pulsatility index and systolic peak velocity found sensitivity and specificity for each index at 77.2 and 89.8%, 80.6 and 79.9%, and 80.0 and 84.2%, respectively 4,17,19 (A)(B). The evaluation of adnexal findings by Doppler study using resistance index, pulsatility index and maximum systolic velocity did not show diagnostic accuracy greater than that of conventional ultrasound.…”
Section: (A)(b)mentioning
confidence: 99%
“…83 Laban et al in a series of 50 masses found that 3D-US had a higher sensitivity and specificity than 2D-US. 84 Some studies have assessed the role of 3D-PDA for discriminating benign from malignant adnexal masses.…”
Section: Three-dimensional Ultrasound In Adnexal Pathologymentioning
confidence: 99%
“…84,[93][94][95][96] Furthermore, this approach is only moderately reproducible. 93,94 These studies are summarized in Table 5.…”
Section: Three-dimensional Ultrasound In Adnexal Pathologymentioning
confidence: 99%